Auricularia polytricha noodles prevent hyperlipemia and modulate gut microbiota in high-fat diet fed mice - Donglu Fang; Dan Wang; Gaoxing Ma; Yang Ji; Huihua Zheng; Hui Chen; Mingwen Zhao; Qiuhui Hu; Liyan Zhao (Food Science and Human Wellness)
Auricularia polytricha possesses hypolipidemic effects and decreases lipid accumulation, leading to potential food additives for functional food processing. In this research, we explored the potential effects of A. polytricha noodles on hyperlipidemia and gut microbiota dysbiosis, and elucidated their possible regulatory mechanisms on lipid metabolism in high-fat diet (HFD) mice. A. polytricha noodles treatment significantly (P < 0.05) reduced body weight gain, hyperlipidemia and liver fat accumulation. Meanwhile, A. polytricha noodles decreased the levels of serum total cholesterol (TC), total triglyceride (TG) and low-density lipoprotein cholesterol (LDL-C) compared with the HFD group. Furthermore, A. polytricha noodles could enrich the diversity of gut microbiota by decreasing the ratio of Firmicutes to Bacteroidetes as well as the relative abundance of Deferribacteres and increased the relative abundance of Verrucomicrobia, which might contribute to the prevention of hyperlipidemia. This study indicated that A. polytricha noodles could modulate the gut microbiota and prevent hyperlipidemia and liver fat accumulation induced by HFD.